Low incidence of adjacent segment disease after posterior lumbar interbody fusion with minimum disc distraction: A preliminary report. Issue 2 (January 2018) - Makino, Takahiro; Honda, Hirotsugu; Fujiwara, Hiroyasu; Yoshikawa, Hideki; Yonenobu, Kazuo; Kaito, Takashi
Abstract: Study Design: A retrospective review of prospectively collected data. Objective: To investigate the incidence of radiographic and symptomatic adjacent segment disease (ASD) and identify possible risk factors for ASD after posterior lumbar interbody fusion (PLIF) with minimum disc distraction by selecting low-height interbody cages. Summary of Background Data: Excessive disc space distraction is reportedly 1 of the risk factors for ASD after PLIF; however, the incidence and other risk factors of ASD after PLIF with minimum disc distraction remain unclear. Methods: Forty-one consecutive patients who underwent PLIF at L4-L5 and were postoperatively followed up for a minimum of 2 years were included. The height and shape (box or bullet shape) of interbody cages was determined according to the disc height and morphology of the intervertebral space assessed on preoperative computed tomography scans to avoid excessive distraction. The incidence of radiographic and symptomatic ASD was evaluated and all demographic and radiographic parameters were compared between patients with and without ASD. Multivariate logistic regression analysis was performed to identify risk factors for ASD among the variables with P < .20 in univariate analysis. Results: The overall incidence of ASD was 12.2% (5/41 patients): radiographic ASD, 7.3% (3 patients); symptomatic ASD, 4.9% (2 patients). Multivariate analysis revealed preoperative retrolisthesis of L3 on extension as the sole risk factor for ASD after PLIF with minimum disc distraction (odds ratio, 2.13; 95% confidence interval, 1.00–4.05; P = .049). Conclusions: The incidence of ASD in this study was lower than that of ASD in our previous study about PLIF with distraction of disc space (12.2% vs. 31.8%). Minimum disc distraction by selection of low-height interbody cages is a simple and effective method to prevent ASD at the surgeons' discretion, although preexisting retrolisthesis at the adjacent upper segment should be taken into consideration.